Microalgae in tilapia ponds and its biotechnology, environmental and industrial potential (Biocenosis, 2013)
Microalgae have been extensively studied worldwide in the tropics but more studies are needed regarding identification and potential biotechnological applications. Tilapia ponds are artificial ecosystems with a high potential for the identification of these microalgae, because their physical and chemical conditions are very stable during the year. This research found 31 species of microalgae in tilapia ponds of the Biological Station of 28 miles in Limon, many of which have been recognized for their biotechnological applications. This places Costa Rica as a place where you can find microalgae of interest in this line of research.
Keywords: Microorganisms; Cyanobacteria; Green algae; Tilapia culture